Assessing fitness for professional and non-professional drivers: legislation and medico-legal issues - Pelizza, Paolo (La Medicina del Lavoro, 2017)
For a long time, European legislation has not considered the Obstructive Sleep Apnea Syndrome (OSAS) a relevant factor for road safety. In Italy, in 2010 the Scientific Society of Legal Medicine COMLAS published Guidelines for the assessment of fitness to drive. An entire chapter, written in collaboration with the Commission “Sleepiness, Safety and Transportation” of the Italian Association of Sleep Medicine (AIMS), is dedicated to the criteria for assessing fitness to drive of people with OSAS or narcolepsy. Only in 2016, following the adoption of European Commission Directive 2014/85/EU, Italian law recognized OSAS as a condition to be considered in the assessment of fitness to drive. The author discusses the ascertainment criteria and the medico-legal implications regarding information to patients and reporting duty.